UML for the IT business analyst : a practical guide to object-oriented requirements gathering - Podeswa, Howard (Australia ; United States : Course Technology/Cengage Learning, 2010)
Business analysts are required to understand object-oriented technology. This guide shows how the Business Analyst can perform his or her role using object-oriented technology.
oif 12/06/15
Loan
Keywords: Object-oriented methods (Computer science); UML (Computer science); Business -- Computer network resources -- Case studies